Conflict and Reconciliation : the Politics of Ethnicity in Assam. - Goswami, Uddipana (Transition in Northeastern India., 2014)
Diverging from reductionist studies of Northeast India and its multifarious conflicts, this book presents an exclusive and intricate, empirical and theoretical study of Assam as a conflict zone. It traces the genesis and evolution of the ethnic and nationalistic politics in the state, and explores how this gave birth to nativist and militant movements. It further discusses how the State's responses seem to have exacerbated rather than mitigated the conflict situation. The author proposes ethnic reconciliation as an effective way out of the current chaos, and finds the key in e.